Effectiveness of capital controls in India: Evidence from the offshore NDF market - Michael Hutchison; Gurnain Kaur Pasricha; Nirvikar Singh (University of California, Santa Cruz Institute for International Economics (SCIIE), 2011)
This paper analyzes the extent to which the effectiveness of international capital controls in India have changed over time by analyzing daily return differentials in the non-deliverable forward (NDF) markets using the self-exciting threshold autoregressive (SETAR) methodology. We begin with a detailed narrative on the evolution of capital controls in India and calculate deviations from covered interest parity utilizing data from the 3-month offshore non-deliverable rupee forward market. We estimate a no-arbitrage band using SETAR where boundaries are determined by transactions costs and by the effectiveness of capital controls. We identify several distinct periods reflecting changes in capital control application and intensity for India, and estimate the model over each sub-sample in order to capture the de facto effect of changes in capital controls on return differentials over time. We find that Indian capital controls are asymmetric over inflows and outflows, have changed over time from primarily restricting outflows to effectively restricting inflows; and that arbitrage activity closes deviations from CIP when the threshold boundaries are exceeded in all sub-samples. Moreover, our results indicate a significant reduction in the barriers to arbitrage since 2008. As a robustness test of the methodology, we also apply the methodology to the Chinese RMB NDF market and find that capital controls vary over time. However, we do not find a pattern indicating a gradual relaxation of capital controls in China.
Keywords: 330